2022
DOI: 10.1101/2022.01.25.477673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Despite the odds: formation of the SARS-CoV-2 methylation complex

Abstract: Coronaviruses protect their single-stranded RNA genome with the methylated cap added during the replication. This capping process is carried out by several nonstructural proteins (nsp) encoded in the viral genome. The methylation itself is performed consecutively by two methyltransferases, nsp14 and nsp16, which interact with nsp10 protein acting as a co-factor. The nsp14 protein also carries the exonuclease domain, which also serves as a part of the proofreading system during the replication of the large RNA … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…We have demonstrated earlier that nsp14, nsp10 and nsp16 form a ternary complex cantered around nsp10 12 . However, such complex is not supported by the structural data available on nsp10/nsp14 and nsp10/nsp16 binary complexes.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…We have demonstrated earlier that nsp14, nsp10 and nsp16 form a ternary complex cantered around nsp10 12 . However, such complex is not supported by the structural data available on nsp10/nsp14 and nsp10/nsp16 binary complexes.…”
Section: Resultsmentioning
confidence: 77%
“…The structural basis of nsp14 interaction with nsp10 has been elucidated 11 . We have recently demonstrated that nsp14, nsp10 and nsp16 form a ternary complex, further modulating nsp14 catalytic activity 12 . Despite the detailed structural characterization of the complexes, the mechanistic basis of the modulation of nsp14 exonuclease activity remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated earlier that nsp14, nsp10, and nsp16 form a ternary complex centered around nsp10 ( Matsuda et al., 2022 ). However, such complex is not supported by the structural data available on nsp10/nsp14 and nsp10/nsp16 binary complexes.…”
Section: Resultsmentioning
confidence: 85%
“…The structural and biochemical basis of nsp14 interaction with nsp10 has been elucidated ( Baddock et al., 2022 ; Liu et al., 2021 ; Lin et al., 2021 ). We have recently demonstrated that nsp14, nsp10, and nsp16 form a ternary complex, further modulating nsp14 catalytic activity ( Matsuda et al., 2022 ). Despite the detailed structural characterization of the complexes, the mechanistic basis of the modulation of nsp14 exonuclease activity remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…While the kinetics for the NSP10/NSP14 complex in isolation is clear, the major limitation of this study and others is that the experiments fail to consider that the exonuclease presumably functions in a complex containing the helicase, RdRp, and potentially other viral nonstructural proteins, which may change the kinetics of RNA hydrolysis and substrate specificity. For example, a recent preprint suggests that the kinetics of exonuclease hydrolysis changes in the presence of NSP16 . Previous studies have clearly shown a robust change in activity upon the association of NSP10 with NSP14, so a further change in activity when complexed with other viral proteins is conceivable.…”
Section: Discussionmentioning
confidence: 99%